Multimodal phenotyping and correlates of pain following hematopoietic cell transplant in children with sickle cell disease. Issue 1 (2nd November 2022) - Bakshi, Nitya; Astles, Rachel; Chou, Eric; Hurreh, Asha; Sil, Soumitri; Sinha, Cynthia B; Sanders, Kolanda Ackey; Peddineni, Manasa; Gillespie, Scott E; Keesari, Rohali; Krishnamurti, Lakshmanan
Abstract: Introduction: There is limited understanding of pain, patient‐reported outcomes (PROs) of health‐related quality of life (HRQoL), psychological factors, and experimental pain sensitivity before and following hematopoietic cell transplant (HCT) in children with sickle cell disease (SCD). Methods: Individuals aged 8 years and older, English speaking, and scheduled for a HCT were invited to participate in an observational study where they completed assessments of pain, PROs, psychological factors, and qualitative interviews before and around 3 months, 6 months, 1 year, and 2 years post‐HCT. An optional substudy of experimental pain sensitivity before and around 6 month, 1 year, and 2 years post‐HCT was also offered. Results: Data from eight participants (median age 13.5 years, 25% female) with sickle cell anemia (SCA) or similarly severe genotype, and successful donor‐derived erythropoiesis post‐HCT are reported. We found that collection of pain, PROs, psychological factors, and qualitative data were feasible in the context of HCT. We found moderate to large differences in pain and some PROs between baseline to 1 year and baseline to 2 year post‐HCT based on effect sizes, but only some differences were statistically significant. We found moderate to large differences in pressure pain threshold and moderate differences in cold pain threshold between baseline to 1 year and baseline to 2 year post‐HCT based on effect sizes, but these differences were not statistically significant. Qualitative data indicated an improvement in pain and HRQoL post‐HCT. Conclusion: This study provides a framework for the conduct of multimodal pain assessments before and after HCT, which is feasible but faced with unique barriers.